The Algorithmic Age: On Dynamic Interactions Shaping Creative Practices (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2024)
Generative Adversarial Networks (GANs) and a panel of selected artworks by the artist Sougwen Chung are analyzed hereafter as paradigmatic and innovative case studies able to express a conception of interactivity intrinsic to the human-mediated relationship with our interconnected world. This paper investigates the manifestation of this feature as constitutive of an artistic practice based on collaboration. By integrating the latest artificial intelligence technologies into their methodologies, these practices become conceptually richer than in the past. The gradations that inform human-system interactions express an interactivity that enhances the creative process not only on a compositional level but also in terms of reworking content that, in their final form, exceed preordained operational mechanisms. I aim to discuss how these two case studies exhibit these traits within a theoretical framework where Visual Arts, mixed with philosophical questioning, are proposed as a preferred point of view to lead reflections and examine the new inquiries arising from the evolution of a technology deeply rooted in the environment we inhabit.
Keywords: GAN; Interactivity; Feedback Loops; Sougwen Chung; Algorithm